The Development of VN Application-Based Learning Videos on Writing Skill of Descriptive Texts for Seventh Grade Students at SMPN 01 Tebo Regency - Salahuddin, Amar; Aprimadedi, Aprimadedi; Sahlan, Sahlan (The Future of Education Journal, 2025)
This study aims to develop an instructional medium using  the VN  application  for  teaching descriptive text writing. The researcher chose the VN application  because  it  is practical and easy  to  use for creating  learning  videos designed to actively engage students’ visual and  auditory senses, there by optimizing  the  absorption  of  the  material. This  research employed a research and development  (R&D)  method with a 4D model, consisting of the stages of define, design, develop, and disseminate. The study was conducted at SMPN 01 Tebo Regency in the 2024/2025 academic year with a research subject of  29  seventh-grade students. Data collection techniques included student  response questionnaires, teacher  responses, and   validation sheets from media experts, material experts, and language experts. The results  showed that  the researcher  success fully  produced  a learning  video as a medium for  teaching  descriptive  text  writing. The media was deemed valid based on expert validations: media expert validation scored  95%  (categorized as “highly valid”), material expert validation scored 85% (“valid”), and language expert validation also scored 85% (“highly valid”). This indicates that the learning video is suitable for use by teachers and students. Furthermore, practicality assessments revealed a score of  96.3%  from  teachers and  97.6%  from students, both categorized as “highly valid.” Thus, it can be concluded that the learning video developed by the researcher is feasible for use, as it meets the criteria of being valid, practical, and effective.